2021
DOI: 10.48550/arxiv.2109.03500
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diffeomorphisms of discs and the second Weiss derivative of BTop(-)

Abstract: A. We compute the rational homotopy groups in degrees up to approximately 3 2 𝑑 of the group of di eomorphisms of a closed 𝑑-dimensional disc xing the boundary. Based on this we determine the optimal rational concordance stable range for high-dimensional discs, describe the rational homotopy type of 𝐡Top(𝑑) in a range, and calculate the second rational derivative of the functor 𝐡Top(βˆ’) in the sense of Weiss' orthogonal calculus. C 1. Introduction 1 2. Automorphisms, self-embeddings, and mapping class grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Remark 4. Lemma A also follows from[4, Proposition 6.4] by Krannich and Randal-Williams, proved by different method. Their class 𝛼 ∈ πœ‹ π‘˜βˆ’1 ( BDif f (𝑉, πœ•)) βŠ— β„š is symmetric in the three handles by definition, whereas it is not obvious for our 𝛽.…”
mentioning
confidence: 79%
“…Remark 4. Lemma A also follows from[4, Proposition 6.4] by Krannich and Randal-Williams, proved by different method. Their class 𝛼 ∈ πœ‹ π‘˜βˆ’1 ( BDif f (𝑉, πœ•)) βŠ— β„š is symmetric in the three handles by definition, whereas it is not obvious for our 𝛽.…”
mentioning
confidence: 79%
“…holds in a range of degrees. This range which is nowadays known to be roughly 2n, by recent work of Krannich [43] and Krannich-Randal-Williams [42]. An instance of Morlet's lemma of disjunction states that the homotopy fibre of…”
Section: Combining This With Ο†U Nmentioning
confidence: 98%
“…In loc.cit., Borel showed that M (SL g (R), (k, l)) β‰₯ g βˆ’ 2, but left C(SL g (R), (k, l)) implicit. A relatively naive counting argument given in the proof of [42,Theorem 7.3] shows that C(SL g (R), (k, l)) β‰₯ 1 8 g 2 βˆ’ max(k, l)βˆ’ 1, which implies that (6.18) is an isomorphism when p ≀ f k,l (g), and f k,l is a function with lim gβ†’βˆž f k,l (g) = ∞.…”
Section: Similarly Let Us Definementioning
confidence: 99%
“…As explained in the outline in Section 1.2.5, the main ingredient besides Theorem 7.24 is work of Boavida de Brito-Weiss' [BdBW18] and work of Fresse-Turchin-Willwacher [FTW17]. We also make use of results of Krannich, Kupers, Randal-Williams, and Watanabe [KrRW21,KuRW21,Wat09], though this can be avoided in most cases (see Remark 8.14).…”
Section: T Cmentioning
confidence: 99%
“…For 𝑑 β‰  4, Corollary 8.8 also follows by combining[Mil09, Lemma 10, p. 188] with [KS77, Essay V. Β§5.0(1)]. The advantage of the proof above is that it applies to 𝑑 = 4.The second result on BTop(𝑑) we will use follows from works of Krannich, Kupers, Randal-Williams, and Watanabe[KrRW21,KuRW21,Wat09]. It concerns two commutative squaresBO(2𝑛) 𝐾 (Q, 2𝑛) Γ— BO BO(2𝑛 + 1) 𝐾 (Q, 4𝑛) Γ— BO BTop(2𝑛) 𝐾 (Q, 2𝑛) Γ— BTop BTop(2𝑛 + 1) 𝐾 (Q, 4𝑛)arrows are induced by the inclusion O(𝑑) βŠ‚ Top(𝑑) and the horizontal arrows by the stabilisation map, the Euler class 𝑒 ∈ H 2𝑛 (BTop(2𝑛); Q), and the odd-dimensional analogue of its square 𝐸 ∈ H 2𝑛+1 (BTop(2𝑛 + 1); Q) (see [KrRW21, Sections 1.2.2 and 8.1.1] for further information on this class).…”
mentioning
confidence: 95%